EMPTY SELLA SYNDROME WITH ECTOPIC GROWTH HORMONE SECRETION: AN UNUSUAL PRESENTATION OF ACROMEGALY - S, Navindran; S, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Empty sella syndrome is a radiological diagnosis characterised either by primary of secondary causes. Individuals with empty sella syndrome do not have any associated symptoms, but some may exhibit features suggestive of hypopituitarism. We report a case of a female with symptoms of florid growth hormone excess with radiological evidence of empty sella syndrome. RESULTS A 59-year-old Malay female was initially referred for poorly controlled diabetes with HBA1c of 12.5% requiring very high doses of insulin. On further history, she claimed that her ring size increased from size 20 at the time she got married to size 25 along with increased shoe size from 7 to size 10 in a span of 6 years. On clinical examination, she had typical features of acromegaly. Formal Bjerrum testing showed normal visual fields. IGF-1 level was elevated at 655ug/L (97-292). Her other anterior pituitary hormonal tests were normal. Her growth hormone (GH) was not suppressed following an oral glucose load (OGTT). Brain MRI revealed non-visualisation of normal pituitary gland with CSF filled sella turcica suggestive of empty sella syndrome. A contrast-enhanced computed tomography revealed a soft tissue density seen at the right lateral aspect of the pituitary fossa which is most likely arising from the sella turcica. She was then referred to neurosurgery. CONCLUSION We described a patient with clinically and biochemically proven acromegaly with an empty sella syndrome on MRI. Early screening and detection would be imperative for earlier neurosurgical referral for better outcome.